Preparation and application of composite filament of melt spinning polyethylene melt coated thermotropic liquid crystal polyarylate fiber

By melt-spinning polyethylene melt-coated thermochromic liquid crystal polyaryle fibers, combined with modified polyethylene resin and thermochromic liquid crystal polyaryle fibers, the wear resistance of thermochromic liquid crystal polyaryle fibers in high-end applications is solved. and the problem of insufficient strength has achieved improved wear resistance of high-strength and high-modes and is suitable for applications in multiple fields.

CN119243366AActive Publication Date: 2025-01-03DONGHUA UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411335729.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The prior art is difficult to meet the requirements of high-strength, high-model and wear resistance of thermochromic liquid crystal polyarylate fibers at the same time. Especially in high-end applications such as parachutes, the wear resistance and strength of the materials are extremely high, and at the same time, it is concentrated during the development process. The problem of poor interfacial adhesion between ethylene and thermogenic liquid crystal polyarylene material.

Method used

The composite wire preparation method of melt-spun polyethylene melt coated with thermochromic liquid crystal polyarylate fibers is used. By combining modified polyethylene resin with thermochromic liquid crystal polyarylate fibers, benzophenone compounds and disulfide compounds are used. Chemical modification, forming reaction sites, triggering the polymerization of phenyl acrylate, and enhancing the overall mechanical properties and wear resistance of the fiber.

Benefits of technology

It significantly improves the tensile strength, tensile modulus and wear resistance of composite wires, maintains high mechanical properties, and reduces dielectric constant and dielectric loss. It is suitable for fishing lines, ropes, obstruction cables, parachutes and other fields. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005058183280000011
    Figure HDA0005058183280000011
Patent Text Reader

Abstract

The invention relates to a high-strength high-modulus wear-resistant thermotropic liquid crystal polyarylester fiber and a preparation method thereof, specifically, polyethylene resin capable of being subjected to melt processing is adopted as a coating material, thermotropic liquid crystal polyarylester fiber is adopted as a core material, the overall wear resistance of a composite filament is effectively improved by utilizing a modification technology, and meanwhile, the original high mechanical property is retained. The tensile strength of the prepared thermotropic liquid crystal polyarylester composite yarn is higher than 20 cN / dtex, the tensile modulus is higher than 600 cN / dtex, the strength retention rate after 10000 times of friction is higher than 80%, and meanwhile the thermotropic liquid crystal polyarylester composite yarn has low dielectric constant (smaller than or equal to 2.5) and dielectric loss (smaller than or equal to 0.005).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-performance chemical fibers and relates to a high-performance thermotropic liquid crystal polymer fiber and a preparation method thereof. Background Art

[0002] Thermotropic liquid crystal polyarylate fiber occupies an important position in the high-performance fiber market due to its excellent mechanical properties and heat resistance. This fiber is not only widely used in the fields of automobiles, cables, slings, etc., but also in the field of parachutes, especially parachutes in spacecraft recovery systems, it also shows its unique value.

[0003] In order to improve the wear resistance of thermotropic liquid crystal polyarylate fibers, researchers have adopted a variety of chemical modification strategies. First, by adjusting the monomer ratio and the use of catalysts, the molecular structure of the fiber can be optimized to improve its wear resistance. For example, by increasing the molar percentage of 5-aminoindole-2-carboxylic acid, the wear resistance of the fiber can be effectively enhanced. In addition, the optimization of solid phase polycondensation reaction is also an important means to improve the wear resistance of the fiber. By reacting in an inert gas atmosphere, fiber products with higher strength and modulus can be produced.

[0004] The application of surface modification technologies, such as plasma treatment and silane coupling agent treatment, is also an effective way to improve the wear resistance of fibers. These technologies can introduce active groups on the fiber surface, enhance the adhesion between the fiber and the matrix, and thus improve the wear resistance. At the same time, the addition of inorganic fillers, such as glass fiber, boron nitride fiber, etc., can also significantly improve the wear resistance of fibers.

[0005] Heat treatment is another key step to improve the wear resistance of fibers. By performing relaxation heat setting in a nitrogen atmosphere, the crystallinity and mechanical properties of the fibers can be improved, thereby enhancing the wear resistance. In addition, the application of ultraviolet radiation grafting modification technology can also effectively improve the wear resistance of fibers by introducing active groups such as acrylic acid on the fiber surface.

[0006] In the field of parachutes, the wear resistance of thermotropic liquid crystal polyarylate fibers is particularly important. The parachutes of spacecraft recovery systems need to withstand extreme mechanical loads and environmental conditions, so there are extremely high requirements for the wear resistance and strength of the materials. Through the above-mentioned chemical modification method, the performance of thermotropic liquid crystal polyarylate fibers has been significantly improved, enabling them to play an important role in key applications such as parachutes (Chinese patent CN 111038707 B).

[0007] In summary, the wear resistance of thermotropic liquid crystal polyarylate fibers has been effectively improved through chemical modification, which not only enhances its application potential in traditional fields, but also provides a solid foundation for its development in high-end application fields such as spacecraft recovery systems. With the continuous advancement of materials science, the performance of thermotropic liquid crystal polyarylate fibers will be further optimized and its application range will continue to expand.

[0008] On the other hand, polyethylene materials have excellent wear resistance, especially ultra-high molecular weight polyethylene (UHMWPE) and its fibers are well-known for their excellent wear resistance, impact resistance, low friction coefficient and good chemical stability, and are widely used in multiple industries. The specific strength of UHMWPE fiber is 15 times that of steel. It has ultra-high strength, ultra-high modulus, low density and excellent chemical corrosion resistance, which makes it ideal for bulletproof, stab-proof security protection materials and high-performance lightweight composite materials. In terms of wear resistance, UHMWPE fiber performs well, and its wear resistance is better than many other materials, including POM (polyacetal), fluorine-containing resin and PA66 nylon. The wear resistance of this material makes it very suitable for high-wear applications such as pipes, bushings, shafts, containers, etc. The wear resistance of UHMWPE increases with the increase of molecular weight, which allows it to replace metal in applications requiring high wear resistance, while also having the advantage of lightweight.

[0009] However, since ultra-high molecular weight polyethylene has a molecular weight of more than 1 million, it is often processed by solution processing, which is complicated and uses high costs for organic solvents. Conventional molecular weight polyethylene can be processed by melt processing, which is lower cost and environmentally friendly, and can be used as a coating layer for thermotropic liquid crystal polyarylate fibers. Therefore, combining thermotropic liquid crystal polyarylate fibers and polyethylene by melt coating is an effective way to improve the wear resistance of thermotropic liquid crystal polyarylate fibers. However, there are also many difficulties in the composite process of the two, such as the poor interface adhesion between polyethylene and thermotropic liquid crystal polyarylate, which requires targeted improvements and the proposal of new process solutions.

[0010] In summary, the existing technology cannot simultaneously meet people's requirements for high strength, high modulus and wear resistance of thermotropic liquid crystal polyarylate fibers. Therefore, it is necessary to develop thermotropic liquid crystal polyarylate fibers with high strength, high modulus and wear resistance to meet the needs of the downstream application market; and it is very necessary to develop new methods and new processes to fully combine polyethylene materials with thermotropic liquid crystal polyarylate materials during the development process. Summary of the invention

[0011] The purpose of the present invention is to break the bottleneck of the existing technical solutions and provide a preparation and application of a composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber. The present invention can be achieved by the following technical solutions:

[0012] The present invention provides a composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber, which has a composite structure (fiber cross-sectional structure such as Figure 1 As shown in FIG. 1 , the main components are thermotropic liquid crystal polyarylate and modified polyethylene. In the composite structure, the mass of the thermotropic liquid crystal polyarylate fiber accounts for 25-95 parts, and the mass of the modified polyethylene resin accounts for 5-90 parts.

[0013] Preferably, the composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber, wherein the thermotropic liquid crystal polyarylate fiber used has a tensile strength of 20-40 cN / dtex, a tensile modulus of 500-1000 cN / dtex, and a weight average molecular weight of the modified polyethylene resin of 20,000-600,000.

[0014] The present invention also provides a method for preparing a composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber, which specifically comprises the following steps:

[0015] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a certain proportion to obtain a modified solution. Polyethylene resin chips are added to the modified solution, and high-purity argon gas is introduced and stirred for a period of time to obtain a solid-liquid mixture.

[0016] Step 2: Use an ultraviolet lamp with a wavelength of 253 nm to irradiate the solid-liquid mixture of step 2 for a period of time, continue to stir and continuously introduce high-purity argon during the irradiation process, and control the temperature of the solid-liquid mixture within a certain range. Stop the ultraviolet lamp irradiation, filter the irradiated solid-liquid mixture, wash it with dichloromethane, and then dry it in an oven at a certain temperature to obtain a modified polyethylene resin slice.

[0017] Step 3: preheating the thermotropic liquid crystal polyarylate fiber (including thermotropic liquid crystal polyarylate monofilament and thermotropic liquid crystal polyarylate multifilament) in air at a certain temperature, and then coating the modified polyethylene resin slice in step 2 on the surface of the thermotropic liquid crystal polyarylate fiber by a screw extruder at a certain temperature, and then cooling to obtain the thermotropic liquid crystal polyarylate composite filament.

[0018] Preferably, in step 1, the chemical structures of (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (hereinafter referred to as benzophenone compound 1) and thioperoxydicarbonic acid ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (hereinafter referred to as disulfide compound 2) are as follows: Figure 2As shown, the molar ratio of benzophenone compound 1, disulfide compound 2 and phenyl acrylate is 1:1:(100-300); the weight average molecular weight of the polyethylene resin slice in step 1 is between 20,000 and 500,000; the purity of argon is greater than 99.999%; the amount of argon introduced is 10-2000 ml / min; the mass ratio of polyethylene resin slice to phenyl acrylate is 1:(0.1-50), and the stirring and nitrogen passing time are the same, which is 5-60 minutes.

[0019] Preferably, in step 2, the amount of argon gas introduced is 10-2000 ml / min, the temperature of the solid-liquid mixture is controlled in the range of 10 to 60 degrees Celsius, and the ultraviolet lamp irradiation time is 3 to 48 hours. During the drying process, the oven temperature is 40-80 degrees, and the drying time is 2-10 hours.

[0020] Preferably, in step 3, the thermotropic liquid crystal polyarylate fibers (including thermotropic liquid crystal polyarylate monofilaments and thermotropic liquid crystal polyarylate multifilaments) are preheated in air at 100-130 degrees Celsius. The screw extruder is set at a temperature of 130-200 degrees Celsius.

[0021] The thermotropic liquid crystal polyarylate composite yarn obtained through steps 1 to 3 of the present invention has a tensile strength higher than 20 cN / dtex, a tensile modulus higher than 600 cN / dtex, and a strength retention rate higher than 80% after rubbing 10,000 times.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: polyethylene is used as the coating material, and thermotropic liquid crystal polyarylate fiber is used as the core material. The composite wire obtained by the melt coating method can effectively improve the wear resistance while retaining the original high mechanical properties; at the same time, the present invention also adopts a modification technology to chemically modify the polyethylene resin before coating, and on the polyethylene molecular chain, a reaction site is formed under the action of a benzophenone compound and a disulfide compound to initiate the polymerization of a monomer such as phenyl acrylate, and successfully graft polyphenyl acrylate. This type of polyethylene resin grafted with polyphenyl acrylate molecular chains has a similar chemical structure to polyarylate, the main component of thermotropic liquid crystal polyarylate fiber. Compared with unmodified polyethylene resin, the method provided by the present invention can effectively improve the bonding force between polyethylene resin and thermotropic liquid crystal polyarylate fiber, and is characterized by having more excellent overall mechanical properties and wear resistance in terms of performance, and the composite wire has a lower dielectric constant (less than or equal to 2.5) and dielectric loss (less than or equal to 0.005).

[0023] The thermotropic liquid crystal polyarylate composite yarn of the present invention can be processed according to the product property requirements, and various other additives can be added during the composite process, such as antioxidants, antistatic agents, flame retardants, pigments, glass fibers, inorganic powders, etc. Suitable application fields include fishing lines, cables, arresting cables, parachutes, etc. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0025] Example 1

[0026] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a molar ratio of 1:1:100 to obtain a modified solution. Polyethylene resin chips with a weight average molecular weight of 100,000 are added to the modified solution, and the mass ratio of polyethylene to phenyl acrylate is 1:10. Argon gas with a purity greater than 99.999% is introduced at a rate of 200 ml / min, and stirred for 30 minutes to obtain a solid-liquid mixture.

[0027] Step 2: The solid-liquid mixture of step 2 was irradiated with an ultraviolet lamp having a wavelength of 253 nm for 12 hours. During the irradiation process, stirring was continued and high-purity argon gas was continuously introduced at a rate of 200 ml / min, and the temperature of the solid-liquid mixture was controlled at 20 degrees Celsius. The ultraviolet lamp irradiation was stopped, and the irradiated solid-liquid mixture was filtered and washed with dichloromethane, and then dried in an oven at 60 degrees Celsius for 3 hours to obtain a modified polyethylene resin slice.

[0028] Step 3: preheat the thermotropic liquid crystal polyarylate fiber in air at a certain temperature of 110 degrees Celsius, then melt-coat the surface of the thermotropic liquid crystal polyarylate fiber with the modified polyethylene resin slice in step 2 at 140 degrees Celsius using a screw extruder, and obtain the thermotropic liquid crystal polyarylate composite yarn after cooling.

[0029] The prepared composite yarn contains 78 parts by weight of thermotropic liquid crystal polyarylate and 22 parts by weight of modified polyethylene resin.

[0030] Example 2

[0031] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a molar ratio of 1:1:150 to obtain a modified solution. Polyethylene resin chips with a weight average molecular weight of 200,000 are added to the modified solution, and the mass ratio of polyethylene to phenyl acrylate is 1:50. Argon gas with a purity greater than 99.999% is introduced at a rate of 500 ml / min, and stirred for 40 minutes to obtain a solid-liquid mixture.

[0032] Step 2: The solid-liquid mixture of step 2 was irradiated with an ultraviolet lamp having a wavelength of 253 nm for 18 hours. During the irradiation process, stirring was continued and high-purity argon gas was continuously introduced at a rate of 500 ml / min, and the temperature of the solid-liquid mixture was controlled at 25 degrees Celsius. The ultraviolet lamp irradiation was stopped, and the irradiated solid-liquid mixture was filtered and washed with dichloromethane, and then dried in an oven at 70 degrees Celsius for 5 hours to obtain a modified polyethylene resin slice.

[0033] Step 3: preheat the thermotropic liquid crystal polyarylate fiber in air at a certain temperature of 115 degrees Celsius, then melt-coat the surface of the thermotropic liquid crystal polyarylate fiber with the modified polyethylene resin slice in step 2 at 145 degrees Celsius using a screw extruder, and obtain the thermotropic liquid crystal polyarylate composite yarn after cooling.

[0034] The prepared composite yarn contains 82 parts by weight of thermotropic liquid crystal polyarylate and 18 parts by weight of modified polyethylene resin.

[0035] Example 3

[0036] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a molar ratio of 1:1:150 to obtain a modified solution. Polyethylene resin chips with a weight average molecular weight of 250,000 are added to the modified solution, and the mass ratio of polyethylene to phenyl acrylate is 1:80. Argon gas with a purity greater than 99.999% is introduced at a rate of 200 ml / min, and stirred for 30 minutes to obtain a solid-liquid mixture.

[0037] Step 2: The solid-liquid mixture of step 2 was irradiated with an ultraviolet lamp having a wavelength of 253 nm for 12 hours. During the irradiation process, stirring was continued and high-purity argon gas was continuously introduced at a rate of 700 ml / min, and the temperature of the solid-liquid mixture was controlled at 20 degrees Celsius. The ultraviolet lamp irradiation was stopped, and the irradiated solid-liquid mixture was filtered and washed with dichloromethane, and then dried in an oven at 80 degrees Celsius for 3 hours to obtain a modified polyethylene resin slice.

[0038] Step 3: preheat the thermotropic liquid crystal polyarylate fiber in air at a certain temperature of 118 degrees Celsius, then melt-coat the surface of the thermotropic liquid crystal polyarylate fiber with the modified polyethylene resin slice in step 2 at 150 degrees Celsius using a screw extruder, and obtain the thermotropic liquid crystal polyarylate composite yarn after cooling.

[0039] The prepared composite yarn contains 85 parts by weight of thermotropic liquid crystal polyarylate and 15 parts by weight of modified polyethylene resin.

[0040] Example 4

[0041] Step 1: Using dioxane as a solvent, (4-methoxyphenyl)(4-(trifluoromethyl)phenyl)methanone (referred to as benzophenone compound 1), thioperoxydicarbonate ([(HS)C(S)]2S2) C,C'-dioctadecyl ester (referred to as disulfide compound 2) and phenyl acrylate are mixed in a molar ratio of 1:1:100 to obtain a modified solution. Polyethylene resin chips with a weight average molecular weight of 300,000 are added to the modified solution, and the mass ratio of polyethylene to phenyl acrylate is 1:150. Argon gas with a purity greater than 99.999% is introduced at a rate of 500 ml / min, and stirred for 55 minutes to obtain a solid-liquid mixture.

[0042] Step 2: The solid-liquid mixture of step 2 was irradiated with an ultraviolet lamp having a wavelength of 253 nm for 20 hours. During the irradiation process, stirring was continued and high-purity argon gas was continuously introduced at a rate of 1000 ml / min, and the temperature of the solid-liquid mixture was controlled at 23 degrees Celsius. The ultraviolet lamp irradiation was stopped, and the irradiated solid-liquid mixture was filtered and washed with dichloromethane, and then dried in an oven at 65 degrees Celsius for 6 hours to obtain a modified polyethylene resin slice.

[0043] Step 3: preheat the thermotropic liquid crystal polyarylate fiber in air at a certain temperature of 120 degrees Celsius, then melt-coat the surface of the thermotropic liquid crystal polyarylate fiber with the modified polyethylene resin slice in step 2 at 180 degrees Celsius using a screw extruder, and obtain the thermotropic liquid crystal polyarylate composite yarn after cooling.

[0044] The prepared composite yarn contains 89 parts by weight of thermotropic liquid crystal polyarylate and 11 parts by weight of modified polyethylene resin.

[0045] Comparative Example 1

[0046] Steps: preheating the thermotropic liquid crystal polyarylate fiber in air at 110 degrees Celsius, then coating the surface of the thermotropic liquid crystal polyarylate fiber with polyethylene resin chips having a weight average molecular weight of 100,000 at 140 degrees Celsius using a screw extruder, and obtaining the thermotropic liquid crystal polyarylate composite yarn after cooling.

[0047] In the prepared composite yarn, the weight of thermotropic liquid crystal polyarylate accounts for 78 parts, and the weight of polyethylene resin accounts for 22 parts.

[0048] Comparative Example 2

[0049] Steps: preheating the thermotropic liquid crystal polyarylate fiber in air at 110 degrees Celsius, then coating the surface of the thermotropic liquid crystal polyarylate fiber with polyethylene resin chips having a weight average molecular weight of 100,000 at 150 degrees Celsius using a screw extruder, and obtaining the thermotropic liquid crystal polyarylate composite yarn after cooling.

[0050] The prepared composite yarn contains 80 parts by weight of thermotropic liquid crystal polyarylate and 20 parts by weight of polyethylene resin.

[0051] The relevant material properties of Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 1.

[0052] Table 1

[0053]

[0054]

[0055] Note: The tensile strength, tensile modulus and dielectric constant in the table are the average values ​​of 20 samples measured under the same processing technology.

[0056] As can be seen from the above table, the tensile strength, tensile modulus and wear resistance of the composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber prepared by the present invention are significantly improved compared with the products obtained by the conventional method, especially the wear resistance index is significantly improved, indicating that the method of the present invention can effectively improve the performance of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 Schematic diagram of the cross-sectional structure of the composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber

[0059] Figure 2 Chemical structural formulas of benzophenone compound 1 and disulfide compound 2.

Claims

1. A composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber, characterized in that: The fiber is mainly composed of thermotropic liquid crystal polyarylate and modified polyethylene resin, wherein the thermotropic liquid crystal polyarylate fiber accounts for 25-95 parts by weight and the modified polyethylene resin accounts for 5-90 parts by weight; The method for preparing a composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber comprises: step (1) premixing a benzophenone compound, a disulfide compound and phenyl acrylate to obtain a modified solution, and then mixing it with polyethylene resin chips; step (2) modifying the solution in argon gas under ultraviolet light irradiation to obtain modified polyethylene resin chips; step (3) using a screw extruder to melt-coat and composite with preheated thermotropic liquid crystal polyarylate fibers, and cooling to obtain a composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fibers.

2. The preparation and application of a composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber according to claim 1, characterized in that: In the step (1), the molar ratio of the benzophenone compound 1, the disulfide compound 2 and phenyl acrylate is 1:1:(100-300), the mass ratio of the polyethylene resin slice to phenyl acrylate is 1:(0.1-50), and the weight average molecular weight of the polyethylene resin slice is 20,000-500,000.

3. The preparation and application of a composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber according to claim 1, characterized in that: The ultraviolet lamp irradiation time in step (2) is 3 to 48 hours.

4. The preparation and application of a composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber according to claim 1, characterized in that: The thermotropic liquid crystal polyarylate fibers described in step (4) include thermotropic liquid crystal polyarylate monofilaments and thermotropic liquid crystal polyarylate multifilaments, which are preheated in air at 100-150 degrees Celsius, and the screw extruder is set at a temperature of 130-200 degrees Celsius.

5. The composite yarn of melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber according to claim 1, characterized in that: The obtained melt-spun polyethylene melt-coated thermotropic liquid crystal polyarylate fiber composite yarn has a tensile strength higher than 20 cN / dtex, a tensile modulus higher than 600 cN / dtex, a strength retention rate higher than 80% after 10,000 frictions, a dielectric constant less than or equal to 2.5, and a dielectric loss less than or equal to 0.005.

Citation Information

Patent Citations

  • Composite fusion filament

    CN111691009A

  • Fluidity improver, thermoplastic resin composition and molding thereof

    JP2021017545A

  • Fluidity improver for aromatic polycarbonate resin, process for producing the fluidity improver for aromatic polycarbonate resin, aromatic polycarbonate resin composition, and molded product

    US20110009567A1

  • Composite fusion filament

    US20200290269A1

  • Thermo-fusible conjugate fibers and method for producing same, and nonwoven fabric using same

    US20200318259A1